The peripheral differentiation of human natural killer T cells. Issue 6 (8th April 2019) - Liu, Jie; Hill, Brenna J; Darko, Sam; Song, Kaimei; Quigley, Máire F; Asher, Tedi E; Morita, Yohei; Greenaway, Hui Y; Venturi, Vanessa; Douek, Daniel C; Davenport, Miles P; Price, David A; et al.
Abstract: The peripheral maturation of human CD1d‐restricted natural killer T (NKT) cells has not been well described. In this study, we identified four major subsets of NKT cells in adults, distinguished by the expression of CD4, CD8 and CCR5. Phenotypic analysis suggested a hierarchical pattern of differentiation, whereby immature CD4 + CD8 − CCR5 − cells progressed to an intermediate CD4 + CD8 − CCR5 + stage, which remained less differentiated than the CD4 − CD8 − and CD4 − CD8 + subsets, both of which expressed CCR5. This interpretation was supported by functional data, including clonogenic potential and cytokine secretion profiles, as well as T‐cell receptor (TCR) excision circle analysis. Moreover, conventional and high‐throughput sequencing of the corresponding TCR repertoires demonstrated significant clonotypic overlap within individuals, especially between the more differentiated CD4 − CD8 − and CD4 − CD8 + subsets. Collectively, these results mapped a linear differentiation pathway across the post‐thymic landscape of human CD1d‐restricted NKT cells. Abstract : We used phenotypic, functional and molecular techniques to map a linear differentiation pathway across the post‐thymic landscape of human CD1d‐restricted NKT cells.